An Analysis of Teachers' Questioning Strategies During Classroom Interaction in Senior High School (A Case Study at One of Senior High School in Pangandaran) - Ardani, Ni’ma Faroidatul; Rohayati, Dedeh; Rustandi, Andi (Universitas Galuh, 2025)
Questioning is known as the most influential teaching skill and frequently used as efficient strategy for teachers in classroom teaching. A question proposed by the teachers can stimulate the students’ learning, gain knowledge, help students build understanding to think critically and creatively, and know the output of the students before or after teaching. Unfortunately, asking questions to the students does not always work well. Sometimes, the teacher fails to engage the students to answer the questions. Therefore, teachers should consider the use of questioning strategies to improve students’ engagement in learning. This study aimed to find out the English teachers’ questioning strategies used by the teachers to improve students’ engagement in classrooms, and to explore the students’ responses toward of the teachers’ questioning strategies. In this study, the method of this study is qualitative research involving one English teachers at on of Senior High School in Padaherang and the students. To collect the data, the researcher used observation and interview. The result of the study showed that the teacher used some questioning strategies,that were: yes/no questions, type short answer/retrieval-style question and display questions. The teacher used their question it’s also related with the condition and material using native language and giving students wait time to think the answers. students' responses to the teacher's questioning strategy, that is has a good effect and can influence class interaction. That students like to answer questions posed by the teacher. When they have difficulty answering these questions in English, they will use Indonesian language. Therefore, the researcher suggested that teachers should be more aware of their questioning skills and use them to improve the students’ engagement in classroom.